Pengelolaan Potensi Wisata Sumber Maron Berbasis Syariah di Pagelaran, Malang - Fatkhul Wahab (LPPI Universitas Al-Qolam Malang, 2024)
The Sumber Maron Tourism Object is managed by Karangsuko BUMdes. Sumber Maron Tourism is semi-autonomous, that is, it has the authority to regulate and develop it. Sumber Maron Tourism Object has a positive impact on the community in improving the economy such as opening stalls, shops and parking. This situation certainly raises a problem, namely competition between them. This research is to find out how the management of Sumber Maron Tourism is a descriptive qualitative research. Data sources include primary sources, namely the village head and his staff, the Sumber Maron tourism manager, and secondary data sources, namely relevant journals and books. Data collection, namely interviews, observations and documents. The results of the study, that Sumber Maron Tourism provides employment to the community. The association was formed, namely the association of traders, parking and motorcycle taxis. Facilities include swimming spots, snorkelling, playing in waterfalls, flying fox, river tubing, PLTMH, toilets, prayer rooms, parking, stalls, shops, tire rental, changing rooms. Sumber Maron Tourism Manager involves the community and economic actors to ensure that tourism objects are not used as places of immorality and prohibit shops and stalls from selling alcohol in these attractions Key words: management; sharia; eco-tourism; community improvement; society